2017
DOI: 10.7880/abas.0170421a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional Factories

Abstract: A questionnaire distributed to domestic factories belonging to Japan's electric and electronics industry revealed three results: (1) regardless of the significant shift of production functions to sites outside Japan, approximately 90% of domestic locations are able to complete production functions to a high degree; (2) approximately 54% of locations are able to complete design functions to a high degree, whereas 24% are able to do so to a low degree; and (3) domestic production sites that are able to completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…In this case, although there is a tendency for costs to increase, overall performance can be improved by integrating many elements (Bennett, 1991). It can be concluded that this fact is compatible with the characteristics and tendencies of other industries in Japan (Takeishi, 2002;Shintaku, 2008;Fukuzawa and Inamizu, 2017), and could be demonstrated to be one of the factors that contribute to the discussion on the comparison of industrial characteristics.…”
Section: Discussionsupporting
confidence: 54%
“…In this case, although there is a tendency for costs to increase, overall performance can be improved by integrating many elements (Bennett, 1991). It can be concluded that this fact is compatible with the characteristics and tendencies of other industries in Japan (Takeishi, 2002;Shintaku, 2008;Fukuzawa and Inamizu, 2017), and could be demonstrated to be one of the factors that contribute to the discussion on the comparison of industrial characteristics.…”
Section: Discussionsupporting
confidence: 54%
“…Despite that, it is more difficult to create collaborative relationships with foreign partners than with domestic partners; customization requests are still the norm in some industries (Nakagawa & Song, 2016). If Japanese companies are able to make proposals to their overseas customers, it is very likely that their domestic production sites will become a strength to them as they globalize (Fukuzawa & Inamizu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…There have been subsequent studies based on the above framework regarding manufacturing strategy and organizational outcomes (Alves, Filho, Nogueira, & Bento, 2015;Boyer & Lewis, 2002;da Silveira & Sousa, 2010;Frohlich & Dixon, 2001;Gonzalez-Benito & Lannelogue, 2014;Joshi, Kathuria, & Porth, 2003;Peng, Schroeder, & Shah, 2011;Rosenzweig & Easton, 2010;Schroeder, Bates, & Junttila, 2002;Ward, Bickford, & Leong, 1996;Ward & Duray, 2000;Ward, Leong, & Boyer, 1994, Ward, McCreery, & Anand, 2007Ward, McCreery, Ritzman, & Sharma, 1998). These studies focused on (1) the relationship between priorities among QCDFs related to competitiveness and organizational outcomes;…”
Section: Manufacturing Strategy As the Core Topic Inmentioning
confidence: 99%